2001
DOI: 10.1093/jac/48.4.515
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Trypanosoma cruzi-infected children with nifurtimox: a 3 year follow-up by PCR

Abstract: Patients suffering from Chagas' disease, as determined by positive serological results, were tested for further evidence of Trypanosoma cruzi infection by xenodiagnosis and PCR. The patients included 67 children aged from 0 to 10 years and 75 adults. All children were positive by PCR on their pre-therapy sample, while only 69% of the seropositive adults and none of the 78 seronegative control adults were PCR positive. Xenodiagnosis was positive in 79% of the children, but only in 21% of the adults. A group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 19 publications
2
57
0
5
Order By: Relevance
“…The 330 bp fragment of the kinetoplast minicircles is normally used as a target for amplification. The PCR assays have shown a variable degree of efficiency, thus a negative result does not necessarily mean that the individual is free of infection because the volume of sample can be insufficient (Solari, 2001). Chiari (1999), reported that an optimized PCR protocol is well correlated with detection of antibodies that induce lysis in trypomastigote forms (CoML) in the presence of complement, indicating active infection in those patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 330 bp fragment of the kinetoplast minicircles is normally used as a target for amplification. The PCR assays have shown a variable degree of efficiency, thus a negative result does not necessarily mean that the individual is free of infection because the volume of sample can be insufficient (Solari, 2001). Chiari (1999), reported that an optimized PCR protocol is well correlated with detection of antibodies that induce lysis in trypomastigote forms (CoML) in the presence of complement, indicating active infection in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was resuspended in 50 µl of water, chromatographed in a P10 filtration microcolumn and stored at -20º C. PCR reactions were performed as described by Solari et al (2001). Briefly, 5 µl of template DNA was amplified in a final volume of 50 µl containing 0.25 mM of each dATP, dCTP, dGTP and dTTP, 200 ng of forward and reverse T. cruzi specific primers 121 (5'-AAATAATG-TACGGG (T/G) GAGATGCATGA3') and 122 (5' GGTTC-GATTGGGGTTGGTGTAATATA3'), 2.5 U of Taq polymerase, 5 µl of 10 × Taq DNA polymerase buffer and 6.7 mM MgCl 2 .…”
Section: Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported in the last 15 years that BZN also exhibits significant curative activity in those with recent onset (up to a few years) of chronic disease; 60-70% of radical parasitological cures have been observed among children up to 14 years of age in Brazil and Argentina (de Andrade et al 1996, Andrade & Zicker 1997, Sosa Estani et al 1998, Sosa Estani & Segura 1999, Andrade et al 2004). On the other hand, other studies in patients of the same age range treated with either BZN or NFX contradict these conclusions (Silveira et al 2000, Solari et al 2001.…”
Section: Relevance Of Specific Chemotherapy For Chagas Disease and LImentioning
confidence: 94%
“…Furthermore, there has been an increase in the use of molecular methods for detecting T. cruzi in blood samples of treated patients 4,7,19,20 .…”
mentioning
confidence: 99%